2020
DOI: 10.3390/fi13010002
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Recommender Systems Based on Emotion Recognition—A Scientometric Review

Abstract: Recommendation systems have overcome the overload of irrelevant information by considering users’ preferences and emotional states in the fields of tourism, health, e-commerce, and entertainment. This article reviews the principal recommendation approach documents found in scientific databases (Elsevier’s Scopus and Clarivate Web of Science) through a scientometric analysis in ScientoPy. Research publications related to the recommenders of emotion-based tourism cover the last two decades. The review highlights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 232 publications
0
28
0
Order By: Relevance
“…Wearables have entered the market in great numbers in recent years [ 9 , 26 ], as have increasingly incorporate sensors that measure physiological signals. The most common sensor present in this type of device is the Photoplethysmogram (PPG) [ 12 , 27 , 28 , 29 ], which registers HR signals.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Wearables have entered the market in great numbers in recent years [ 9 , 26 ], as have increasingly incorporate sensors that measure physiological signals. The most common sensor present in this type of device is the Photoplethysmogram (PPG) [ 12 , 27 , 28 , 29 ], which registers HR signals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Preliminarily, the literature review was conducted to identify the components of the emotion-based tourism recommender frameworks [ 9 ]. This study showed the gap in integrating physiological data from wearable sensors to detect the affective condition of the user as a relevant contextual factor in the satisfaction of the recommendation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, researchers focus their interest on the development of applications based on ontologies. Such is the case of the scientometric review that we preliminarily carried out on the frameworks of tourist recommendation systems [25] that use heterogeneous data sources extracted from wearable devices, the IoT, social networks, and ontologies. A specific application we found is the TRSO [26] recommendation system for tourists to know the attractions they can see and the activities they can do.…”
Section: Related Workmentioning
confidence: 99%